Study of Pop Culture Representation in Social Media - Alifah, Aurelia (Enigma Institute, 2023)
Pop culture has become an inseparable part of modern society's life. Social media, as one of the main platforms for pop culture, has become an effective means for distributing and consuming pop culture. However, the representation of pop culture on social media also often causes problems, such as discrimination, bias and hegemony. This study discusses the representation of pop culture on social media, especially in Indonesia. This study uses a cultural studies approach to analyze the representation of pop culture on social media. The results of the analysis show that the representation of pop culture on social media in Indonesia is still dominated by Western pop culture, and often causes problems, such as discrimination against local culture.